Analysis of the Impact Study of the Inclusive and Sustainable Development of the Smart City of the Indonesian Archipelago Capital (IKN): Mix Methods Study - Syailendra, Mira; Annisa Tri Hanggono (Arkus, 2024)
The Indonesian government plans to build a new National Capital (IKN) in East Kalimantan with an inclusive and sustainable smart city concept. IKN development is expected to have a positive impact on various aspects, such as the economy, social and environment. This research uses a mixed methods method, which combines qualitative and quantitative methods. Qualitative data was obtained through interviews with experts and stakeholders, while quantitative data was obtained through surveys of the community. The research results show that the development of IKN has the potential to have a significant positive impact on the economy, social and environment. However, there are several potential negative impacts that need to be considered and mitigated. The development of IKN can be a great opportunity for Indonesia to create an inclusive and sustainable smart city. However, careful planning and implementation is needed to maximize positive impacts and minimize negative impacts.